The new potty - Mayer, Gina.; Mayer, Mercer 1943-. (New York Golden Books, 2003)
A big brother helps his little sister learn to use the potty.
"Mercer Mayer's Little Critter."
Keywords: Toilet training -- Stories; Brothers and sisters -- Stories